Language attitudes in an Egyptian discourse community - Reigh, Emily (AUC Knowledge Fountain, 2014)
This study investigates language attitudes in an elite university in Egypt, addressing all codes spoken in the community: Fusha (Classical Arabic/Modern Standard Arabic), Egyptian Arabic, English and Egyptian Arabic-English code-switching. Some attitudinal research in the region has been conducted (e.g. Bentahila, 1983; Chakrani, 2011; Lawson & Sachdev, 2000), though most neglects to position the discourse community in larger society and uses limited methodological approaches. In this study, attitudes are interpreted with attention to prevailing language ideologies, including the notion of a standard language, tension between modernity and tradition and language as symbolic capitol. Overt and covert attitudes in terms of both status and solidarity were discerned through a questionnaire, a matched-guise study and group interviews. The discourse community was found to be close-knit, with members viewing themselves as distinct from the rest of Egyptian society. Participants all had a strong command of English, though they varied in Fusha proficiency. Mixed attitudes toward Fusha emerged, in terms of both prestige and importance for maintaining Egyptian/Arab identity. Egyptian Arabic ranked low for status traits, though the variety was ascribed covert prestige in terms of solidarity for males. English was viewed positively as a language of both status and solidarity. Though overt attitudes toward code-switching were ambivalent, covert attitudes toward code-switching were generally positive, a novel finding. This study offers a paradigm for detailed analysis of the language attitudes of a community. Further, it demonstrates the growing favor of English as a language of economic power and explores code-switching as a prestigious in-group language that allows negotiation of modern and traditional identities amongst the privileged classes in Egypt.